Work Values Fit and Subjective Career Success: The Moderating Role of Work Engagement - Sevgi Elmas-Atay (International Review of Management and Marketing, 2017)
Despite the literature suggesting that person-organisation work values fit lead positive work related outcomes, there is no empirical evidence for its effect on subjective career success. The purpose of this paper is to investigate the relationships of four dimensions of person-organisation work values fit (comfort and security, competence and growth, status and independence as well as, social aspects) and subjective career success including whether work engagement moderates these relationships. The sample comprises 364 white-collar workers in Istanbul, with hierarchical multiple regression analyses being used to test the hypotheses. The results show that all four dimensions of work values fit are positively related to subjective career success. In regard to the moderating effect, work engagement is found to have a significant effect on the relationships between status and independence work values fit - subjective career success as well as competence and growth work values fit - subjective career success.